Implementasi Manajemen Pembiayaan dalam Pemeliharaan Sarana dan Prasarana Pembelajaran Madrasah Aliyah di Kabupaten Bandung - M Hijrah M Saway; Ara Hidayat (MANAZHIM, 2019)
Facilities and infrastructure resources (such as the availability of learning tools or facilities that are quantitatively, qualitatively, classrooms appropriate to the number of students, school buildings that are relevant to the needs) are important inputs needed for ongoing education in schools. This research is a field research using purposive sampling which aims to analyze the findings of research relating to the planning and funding sources of funds, the implementation and budgeting of funding funds, evaluation of funding funds in the maintenance of learning facilities and infrastructure. This type of research is descriptive qualitative using data collection techniques in the form of observation, interviews, and documentation. After collecting various types of data related to the research problem, then verify the validity of the research data by triangulating the data. The results of this study indicate that the planning of funding sources in Madrasah al-Ikhlas Cicalengka through the analysis of the activities of the use of financial resources and the activities of institutions while the source of funds in Madrasah Aliyah al-Ikhlas and contributions from the community which are then used to finance programs or school activities such as improvement and maintenance of school facilities and infrastructure and teacher payroll. Budgeting of funds used for maintenance of facilities and infrastructure is good. The use of funds sourced from the central or regional government, especially for the maintenance of facilities and infrastructure, teacher salaries, and improvement of buildings has been done optimally.